2015
DOI: 10.1118/1.4905050
|View full text |Cite
|
Sign up to set email alerts
|

Toward adaptive radiotherapy for head and neck patients: Uncertainties in dose warping due to the choice of deformable registration algorithm

Abstract: The authors evaluated several DIR algorithms for CT-to-CBCT registrations. In spite of all methods resulting in comparable geometrical matching, the choice of DIR implementation leads to uncertainties in dose warped, particularly in regions of high gradient and/or poor imaging quality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
71
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(76 citation statements)
references
References 52 publications
2
71
0
1
Order By: Relevance
“…It has been shown that DIR error is specific to the algorithm used27, 28 and image quality 22. In this study, only one commercial algorithm was used to evaluate the utility of applying DIR to CBCT studies using an unmodified commercial product.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that DIR error is specific to the algorithm used27, 28 and image quality 22. In this study, only one commercial algorithm was used to evaluate the utility of applying DIR to CBCT studies using an unmodified commercial product.…”
Section: Discussionmentioning
confidence: 99%
“…Typical plan adaptation strategies revolve around re‐planning on the CBCT study using DIR to propagate contours and evaluate dose 30, 31, 32. Two publications by Veiga et al have evaluated the process of using DIR to CBCT studies for determining daily dose23 and accumulated dose with different DIR algorithms,28 but in both cases dose computations are needed for each fraction. In this study, DIR of the daily CBCT study is proposed to evaluate anatomical changes without a re‐scan of the patient or dose calculation using a commercial DIR algorithm.…”
Section: Discussionmentioning
confidence: 99%
“…To use the deformable image registration to deform the dose distribution back to the planning CT, a voxel‐by‐voxel accuracy of the deformable image registration would be required 19. On CBCT, which suffers from poor soft tissue contrast and image artifacts, the target volumes as well as the organs at risk (OARs) are not well visible.…”
Section: Methodsmentioning
confidence: 99%
“…All these approaches have been extensively used for DIR validation, and guidelines on their application in the framework of contour propagation have recently been published in the AAPM report 132 . It is important to underline that the geometric accuracy of the propagated contours of anatomical regions does not necessarily mean that their interior is correctly handled, depending on the physical proprieties of the applied DVF . Hence, some groups proposed methods based on inverse consistency metrics or related to the Jacobian of the deformation fields to assure the plausibility of the physical characteristic of DVFs for clinical implementation of dose warping.…”
Section: Introductionmentioning
confidence: 99%